2014
DOI: 10.1007/s00464-014-3950-7
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal versus extracorporeal anastomosis. Results from a multicentre comparative study on 512 right-sided colorectal cancers

Abstract: Our results are encouraging to consider the intracorporeally approach the better way to fashion the anastomosis after laparoscopic right colectomy. This study clearly provides the rationale for a randomized clinical trial, which would be useful to give definitive conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
100
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 49 publications
12
100
4
Order By: Relevance
“…In the present series, although an earlier recovery of gas and bowel function was reported in the IA group, the 2 groups experienced a similar length of stay and incidence of postoperative ileus. These results are in line with the experience of the majority of authors who have analyzed the outcome of IA vs. EA in the nonobese population [4,5,14,15,25] and with our recent interim analysis of a Randomized Controlled Trial on the same subject [12]. In the aforementioned study, a similar length of stay was reported in the 2 groups, despite an earlier recovery of bowel function, and a lower incidence of postoperative ileus was observed in the IA.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present series, although an earlier recovery of gas and bowel function was reported in the IA group, the 2 groups experienced a similar length of stay and incidence of postoperative ileus. These results are in line with the experience of the majority of authors who have analyzed the outcome of IA vs. EA in the nonobese population [4,5,14,15,25] and with our recent interim analysis of a Randomized Controlled Trial on the same subject [12]. In the aforementioned study, a similar length of stay was reported in the 2 groups, despite an earlier recovery of bowel function, and a lower incidence of postoperative ileus was observed in the IA.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were reported by 4 recent meta-analyses, comparing the 2 surgical techniques in the nonobese population [8][9][10][11][12]. This finding is most likely multifactorial [8][9][10][11][12]14]. The high surgical volume of the center, the completion of the learning curve for IA anastomosis before starting the present trial, the presence of a dedicated surgical team might be considered, since LPS right colectomy with IA emerged as one of the most difficult LPS colorectal procedures, suggesting for a longer learning curve [22].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the complications of colon cancer surgery, anastomotic leakage after colon cancer surgery not only increased duration of hospital day and mortality rate, but also worsened the long-term oncological outcome (14). Typically, the percentage of anastomotic leakage in colon surgery has been reported to be below 8% (9,10,13,15,16). In this study, the incidence of anastomotic leakage was 2.2% for HS, 1.6% for FEEA and none for TRI, indicating a relatively low percentage when compared to past reports.…”
Section: Discussionmentioning
confidence: 99%
“…In laparoscopic surgery, intestinal anastomosis is frequently performed extracorporeally due to difficulty with intracorporeal anastomosis connected to technical reasons (15). However, a broader intestinal mobilization and dissection are required for extracorporeal anastomosis in laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%